2012
DOI: 10.4103/0976-500x.99428
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study to compare the effects of pre,intra and post operative steroid (dexamethasone sodium phosphate) on post tonsillectomy morbidity

Abstract: Objective:To determine the effectiveness of dexamethasone on post tonsillectomy morbidities in patients with chronic tonsillitis.Materials and Methods:In this randomized double-blind study, 100 patients who underwent tonsillectomy were enrolled and were randomly allocated into control or dexamethasone group (pre operative, intra operative and post operative groups). Patients were assessed for pain nausea, vomiting and oral intake in the post operative period at 24 h.Results:Patients treated with dexamethasone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…This was reflected in our study, as children demonstrated wide intake ranges as noted above, and were still offered discharge home without major complication. Analyzing oral intake in the postoperative setting across both age cohorts, no absolute value or interval change in oral intake reliably predicted the decision to discharge, continue observation, or offer interventions to patients in either the planned inpatient or expected outpatient cohorts, consistent with prior reports . Despite the growing body of evidence against utilizing adequate oral intake as a criterion for discharge, many would still be uncomfortable discharging a patient whose oral intake is modest or nil for fear of an adverse event.…”
Section: Discussionsupporting
confidence: 67%
“…This was reflected in our study, as children demonstrated wide intake ranges as noted above, and were still offered discharge home without major complication. Analyzing oral intake in the postoperative setting across both age cohorts, no absolute value or interval change in oral intake reliably predicted the decision to discharge, continue observation, or offer interventions to patients in either the planned inpatient or expected outpatient cohorts, consistent with prior reports . Despite the growing body of evidence against utilizing adequate oral intake as a criterion for discharge, many would still be uncomfortable discharging a patient whose oral intake is modest or nil for fear of an adverse event.…”
Section: Discussionsupporting
confidence: 67%
“…Steroids inhibit the production of inflammatory cell factors such as cytokines in macrophages, monocytes, and lymphocytes and decrease extravasation of leucocytes, release of lysosomal enzymes, and vascular permeability in areas of injury leading to reduction in edema and fibrosis during healing. They also block the cyclooxygenase and lipoxygenase pathways by inhibiting phospholipase enzymes and relieve pain by reducing prostaglandin production . Together, these activities lessen the degree of inflammation and its accompanying signs and symptoms, and they are potentially beneficial for all forms of morbidity experienced by patients following tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%
“…28 Another study compared preoperative, intraoperative, and postoperative administration of the study medication with placebo. 42 There were 17 singledose and 12 multiple-dose studies. In studies that compared more than one analgesic with placebo, only one study arm was analysed.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…26 We converted pain intensity values to a 0e10 scale when a 0e5 scale was used in a study. Pain intensity scales of 0e6 and 0e4 were used in one dexamethasone study 42 and in one gabapentin study, 44 respectively; in these studies, we considered that converting values to 0e10 scales would not be appropriate, and they were excluded from pain intensity comparisons in meta-analyses.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation